2014
DOI: 10.1155/2014/376326
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNALet-7and Its Major Targets in Prostate Cancer

Abstract: Prostate cancer is worldwide the sixth leading cause of cancer related death in men thus early detection and successful treatment are still of major interest. The commonly performed screening of the prostate-specific antigen (PSA) is controversially discussed, as in many patients the prostate-specific antigen levels are chronically elevated in the absence of cancer. Due to the unsatisfying efficiency of available prostate cancer screening markers and the current treatment outcome of the aggressive hormone refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 174 publications
(259 reference statements)
0
45
1
1
Order By: Relevance
“…More recently, Shen et al (2015) reported that the single-nucleotide polymorphism in the promoter region of let-7 family is strongly associated with susceptibility to lung adenocarcinoma in Chinese individuals, especially in females who are more than 60 years old. In addition, aberrant expression of let-7 has also been observed in many other human malignancies (Ma et al, 2014), with a distinct expression pattern in cancer development (Boyerinas et al, 2010;Wagner et al, 2014). It has been reported that the let-7 family expression is closely associated with pathologic classification in lung cancer (Esquela-Kerscher et al, 2008;Kumar et al, 2008;Trang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Shen et al (2015) reported that the single-nucleotide polymorphism in the promoter region of let-7 family is strongly associated with susceptibility to lung adenocarcinoma in Chinese individuals, especially in females who are more than 60 years old. In addition, aberrant expression of let-7 has also been observed in many other human malignancies (Ma et al, 2014), with a distinct expression pattern in cancer development (Boyerinas et al, 2010;Wagner et al, 2014). It has been reported that the let-7 family expression is closely associated with pathologic classification in lung cancer (Esquela-Kerscher et al, 2008;Kumar et al, 2008;Trang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a double-negative feedback loop between let-7 and c-Myc has been well established (Kolenda et al, 2014;Sampson et al, 2007;Wagner et al, 2014;Wang et al, 2012). Therefore, to further investigate the mechanism of the let-7adf cluster in regulating the uptake and utilization of glutamine in activated B cells, we examined the expression of c-Myc in the let-7adf cluster KO B cells.…”
Section: Comprehensive Repression Of All Let-7 Mirnas Enhances Igm Prmentioning
confidence: 99%
“…Here, we demonstrate that PAR-2 activation suppresses three antiinflammatory microRNAs: let-7d, miR-23b, and miR-200c. let-7d has been shown to target pro-inflammatory mRNAs encoding IL6, IL13, and TLR4 (47)(48)(49). miR-23b limits tissue inflammation via suppression of Nf-B activation and inflammatory cytokine expression by targeting TAB2, TAB3, and IKK␣ (50).…”
Section: Par-2-mediated Nf-b Activation Suppresses Micrornamentioning
confidence: 99%